Association of Random Blood Sugar with Body Mass Index in Habitants of Suburban Kathmandu District - Singh, Neeti; Sherpa, Ang Tshering; Pandey, Srijana; Pradhan, Amita (Journal of Chitwan Medical College, 2019)
Background: Diabetes mellitus is increasing in alarming number worldwide. The main predisposing factor being daily lifestyle which leads to obesity and other complications. Early diagnosis and life style modification among high risk group can decrease the burden of disease. This study was done to find out the random blood sugar level and assess the relationships between body mass index (BMI), waist hip ratio (WHR) and random blood sugar among the study population. Methods: A cross sectional study was done using retrospective data collected at the health camp conducted during month of October 2018. The study area was Nagarjun and Chandragiri municipalities of Kathmandu district. The data was analyzed using SPSS version 21. The chi square test was used to assess relation between BMI,WHR and Random blood sugar. Results: The number of participants in this study was 274. Majority of the participants, (92.7%) had random blood sugar level 200mg/dl or less. Those having RBS of more than 200mg/dl were 7.3%. Among all participants, 16.06% were obese. Further the obese participants showed high waist hip ratio in 81.8% and 9.1% of them had moderate or low waist hip ratio. Further, 46 participants showed diabetic blood sugar level and were either overweight (39.13%) or obese (28.26%). Conclusions: This study concluded that those who had diabetic blood sugar level or high waist hip ratio had increases BMI. So such screening and preventive programme should be further expanded and even at clinical level. Additionally, patients must be counseled the reason for measuring BMI and RBS and its application for their health promotion.